Double-layer self-healing microcapsule, self-healing asphalt mixture and preparation method thereof
By using double-layer self-healing microcapsules and shape memory fibers in asphalt pavement, the problem of vulnerability of asphalt pavement is solved, rapid self-repair and efficient maintenance are achieved, and crack resistance and durability of the pavement are significantly improved.
Patent Information
- Application Number
- CN202411194453.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing technology is difficult to fundamentally solve the problems of vulnerability and difficulty in repairing asphalt pavements. Traditional repair methods have the disadvantages of long construction cycles, high costs and passive responsiveness.
Using a double-layer self-healing microcapsule, including a capsule shell formed from polycarbonate and polyvinyl alcohol and a healing agent mixed with hydrogenated bisphenol A-type epoxy resin and pentaerythritol tetra-3-mercaptopropionate, combined with shape memory polymer Fiber and carbonyl iron powder form a self-healing asphalt mixture to achieve automatic detection and repair.
It realizes fast and accurate self-healing functions, extends the service life of the road surface, reduces maintenance costs and traffic interruption time, and improves the crack resistance, durability and self-healing efficiency of the road surface.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road engineering materials, and specifically to a double-layer self-healing microcapsule, a self-healing asphalt mixture and a preparation method thereof. Background Art
[0002] Asphalt pavement is the cornerstone of modern transportation infrastructure, and its stable and durable performance is directly related to the efficiency and safety of transportation. With the continuous increase in traffic volume and the frequent occurrence of extreme climate events, asphalt pavement faces unprecedented challenges, among which the generation of pavement cracks is particularly noteworthy. These cracks not only accelerate the aging process of the pavement and reduce its service life, but may also become channels for water infiltration, further aggravating roadbed damage and even threatening driving safety. Traditional pavement repair methods, such as filling cracks and re-paving, can restore pavement functions to a certain extent, but often have the disadvantages of long construction period, high cost, and easy traffic interruption. More importantly, these repairs are often passive responses, that is, intervention is carried out only after cracks appear and significantly affect pavement performance, which is difficult to fundamentally solve the problem of pavement fragility. Therefore, the development of self-healing asphalt pavement technology and the realization of automatic detection and repair of pavement damage have become a research hotspot in the field of road engineering in recent years.
[0003] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0004] Based on at least one of the above problems, the present application provides a double-layer self-healing microcapsule, a self-healing asphalt mixture and a preparation method thereof, aiming to fundamentally solve the technical problem that asphalt pavements are easily damaged and difficult to repair.
[0005] According to the first aspect of the present disclosure, it relates to a double-layer self-healing microcapsule, which includes, from the outside to the inside, a thermosensitive shell, a capsule shell, and a healing agent filled in the capsule shell; the capsule shell is formed by curing a polycarbonate organic solution, and the thermosensitive shell is formed by curing a polyvinyl alcohol solution; in terms of mass percentage, the healing agent is formed by mixing and emulsifying 45-55% of hydrogenated bisphenol A epoxy resin and 45-55% of pentaerythritol tetrakis-3-mercaptopropionate.
[0006] In some embodiments of the present disclosure, the mass fraction of the polycarbonate organic solution is 70-80%; the mass fraction of the polyvinyl alcohol solution is 20-30%.
[0007] According to a second aspect of the present disclosure, a method for preparing the above-mentioned double-layer self-healing microcapsule is provided, comprising the following steps: (1) mixing hydrogenated bisphenol A epoxy resin and pentaerythritol tetrakis-3-mercaptopropionate to form an emulsion; (2) adding the emulsion dropwise to a rotating polycarbonate organic solution so that the polycarbonate organic solution wraps the emulsion droplets, and then volatilizing and removing the organic solvent to solidify and form a capsule shell to obtain a microcapsule suspension; (3) After emulsifying the obtained microcapsule suspension to form a stable emulsion, the emulsion is added into a polyvinyl alcohol aqueous solution and the temperature is adjusted to 20-25° C. so that the polyvinyl alcohol solidifies outside the capsule shell to form a heat-sensitive shell, thereby obtaining a microcapsule suspension; (4) The microcapsule suspension obtained in step (3) is washed, centrifuged at 4500-5500 rpm for 12-18 min, and then filtered and dried to obtain double-layer self-healing microcapsules.
[0008] According to the third aspect of the present disclosure, it relates to a self-healing asphalt mixture, which is made of the following raw materials in parts by weight: 100 parts of mineral material, 4 to 6 parts of asphalt, 0.2 to 0.4 parts of the above-mentioned double-layer self-healing microcapsules, 0.05 to 0.15 parts of shape memory polymer fibers, and 0.02 to 0.04 parts of carbonyl iron powder.
[0009] In some embodiments of the present disclosure, the self-healing asphalt mixture is made of the following raw materials in parts by weight: 100 parts of mineral material, 5.0 parts of asphalt, 0.3 parts of the above-mentioned double-layer self-healing microcapsules, 0.1 parts of shape memory polymer fibers, and 0.03 parts of carbonyl iron powder.
[0010] In some embodiments of the present disclosure, the asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt or SBR modified asphalt.
[0011] In some embodiments of the present disclosure, the mineral material consists of coarse aggregate, fine aggregate and mineral powder.
[0012] In some embodiments of the present disclosure, the shape memory polymer fiber is a polyurethane shape memory fiber.
[0013] According to a fourth aspect of the present disclosure, a method for preparing the self-healing asphalt mixture is provided, comprising the following steps: (1) Double-layer self-healing microcapsules were prepared by the above method; (2) Preparation of carbonyl iron powder modifier: Dry the carbonyl iron powder at 140-160°C for 35-45 minutes for dehydration; (3) Preparation of composite modified asphalt: heat the asphalt to melt at 170-190°C, then add double-layer self-healing microcapsules, shape memory polymer fibers and carbonyl iron powder at 35-45°C, then stir at 170-190°C for 55-65 min, and finally place it at 145-165°C for swelling and development for 25-35 min. (4) Preparation of self-healing asphalt mixture: Mix the mineral material heated to 175°C to 180°C and the composite modified asphalt and stir them evenly to obtain the self-healing asphalt mixture.
[0014] In some embodiments of the present disclosure, in the step (3), after the composite modified asphalt is prepared, it is cooled by gradual cooling; the stirring method is magnetic stirring, first stirring at a stirring rate of 4000-5000 r / min for 15-25 min, and then stirring at a stirring rate of 5000-6000 r / min for 35-45 min.
[0015] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. The double-layer self-healing microcapsule of this application precisely encapsulates the high-efficiency healing agent. When fine cracks appear on the asphalt pavement, the shell of the double-layer self-healing microcapsule ruptures under stress or temperature changes, and automatically releases the healing agent to the damaged area, achieving rapid and precise self-repair function, greatly extending the service life of the pavement, reducing maintenance costs and traffic interruption time.
[0016] 2. This application uses polycarbonate and polyvinyl alcohol as capsule shell materials. Polycarbonate ensures the toughness and durability of the capsule shell based on its excellent mechanical strength and thermal stability, and can effectively protect the internal healing agent from the influence of the external environment; while polyvinyl alcohol enables the capsule shell to decompose rapidly under appropriate conditions and release the healing agent in time based on its good biocompatibility and water solubility. Hydrogenated bisphenol A epoxy resin and pentaerythritol tetra-3-mercaptopropionate together constitute an efficient healing agent system. When the material is damaged, such as cracks, the healing agent is activated, and the thiol in pentaerythritol tetra-3-mercaptopropionate reacts with the epoxy group of hydrogenated bisphenol A epoxy resin to form a strong cross-linked network, thereby building a new molecular bridge in the crack area, sealing the crack and restoring the continuity and mechanical properties of the material, showing good self-healing ability.
[0017] 3. The shape memory polymer fibers introduced in this application bring unique shape recovery capabilities to asphalt mixtures. Under high temperature and external forces, these fibers can remember and recover to their original shape, effectively filling and locking cracks, and enhancing the overall stability and fatigue resistance of the mixture. At the same time, the dispersed distribution of the fibers helps to evenly transfer stress, avoid local stress concentration, and improve the bearing capacity and durability of the road surface.
[0018] 4. This application uses carbonyl iron powder as a highly efficient thermal energy conversion medium, which can quickly generate heat under the action of an electromagnetic field, locally heat the crack area, and significantly accelerate the release rate of the healing agent in the double-layer self-healing microcapsule and the recovery process of the shape memory polymer fiber, thereby ensuring excellent self-healing efficiency even under low temperature or rapid repair requirements, and realizing rapid response repair under self-energy regulation.
[0019] 5. This application integrates the self-healing self-energy of double-layer self-healing microcapsules, the mechanical enhancement and structural adaptability of shape memory polymer fibers, and the rapid thermal response ability of carbonyl iron powder. When damage occurs, the double-layer self-healing microcapsules quickly form a stable cross-linked network through the thiol-epoxy reaction, effectively sealing the cracks and restoring the structural integrity of the material. At the same time, after the material is damaged, the shape memory polymer fiber, with its unique ability to reverse deformation, assists the healing agent to be better distributed in the crack area, promoting physical filling and chemical bonding during the healing process. The addition of carbonyl iron powder, in addition to enhancing the electromagnetic responsiveness of the material, may also promote the flow and diffusion of the healing agent through the local heating effect, accelerate the process of the healing reaction, and achieve a more efficient and comprehensive self-repair effect. Under the combined effect of the three, the crack resistance, durability, self-healing efficiency and environmental adaptability of the asphalt pavement are significantly improved. This multi-dimensional performance improvement provides an advanced material solution for building a more self-energy, green and long-life transportation infrastructure. DETAILED DESCRIPTION
[0020] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0021] Unless otherwise specified, the raw materials and auxiliary raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, detection methods and test methods involved are all conventional methods unless otherwise specified.
[0022] The self-healing asphalt mixture in the following embodiments includes the following preparation steps: (1) Prepare the raw materials according to the weight ratio of 100 parts of mineral material, 4-6 parts of asphalt, 0.2-0.4 parts of double-layer self-healing microcapsules, 0.05-0.15 parts of shape memory polymer fibers (polyurethane shape memory fibers, purchased from Yantai Taihe New Materials Co., Ltd.), and 0.02-0.04 parts of carbonyl iron powder.
[0023] (2) Preparation of double-layer self-healing microcapsules: First, hydrogenated bisphenol A epoxy resin and pentaerythritol tetra-3-mercaptopropionate solution are emulsified by ultrasonic treatment to form a stable oil-in-water emulsion, and then the emulsion is slowly added dropwise to a rotating polycarbonate solution to form the first layer of microcapsule shell using phase separation technology. The organic solvent is then removed by evaporation to solidify the first layer of shell. Subsequently, the first layer of microcapsule suspension is subjected to a gentle emulsification process to form a stable emulsion again, and then added dropwise to a polyvinyl alcohol aqueous solution. The temperature is adjusted to 20-25°C to promote the deposition and solidification of polyvinyl alcohol on the surface of the microcapsule to ensure its structural stability and form a second layer of biodegradable thermosensitive shell. Finally, the microcapsule suspension is washed several times to remove unreacted raw materials and by-products, and then centrifuged at 5000 rpm for 15 min. Finally, it is filtered and dried to separate the double-layer self-healing microcapsules.
[0024] (3) Preparation of carbonyl iron powder modifier: The carbonyl iron powder was placed in an oven at 150°C and dried for 40 minutes for dehydration, thereby obtaining the prepared carbonyl iron powder modifier.
[0025] (4) Preparation of composite modified asphalt: The asphalt was heated to melt at 180°C, double-layer self-healing microcapsules, shape memory polymer fibers and carbonyl iron powder were mixed in a mass ratio of 3:1:0.3 and added to the molten asphalt at 40°C. The mixture was then stirred at 180°C for 60 min at high speed and then placed in an environment of 155°C for swelling and development for 30 min. Finally, the composite modified asphalt was cooled by gradual cooling.
[0026] (5) Preparation of self-healing asphalt mixture: Mix the mineral material heated to 175° C. and the composite modified asphalt in a conventional manner and stir them evenly to obtain the self-healing asphalt mixture.
[0027] Wherein, in the step (4), the stirring method is magnetic stirring, first stirring at a stirring rate of 4500 r / min for 20 min, and then stirring at a stirring rate of 5500 r / min for 40 min.
[0028] The self-healing asphalt mixture induced healing test in the following examples includes the following steps: (1) Cut each Marshall specimen into four equal semi-cylindrical specimens with a length of 100 mm, a height of 50 mm, and a thickness of 30 mm, and cut a notch with a length of 5 mm and a depth of 10 mm at the center of the bottom of the specimen; (2) The specimens were placed in a constant temperature environment of -10°C for 3 h for pretreatment before testing to provide brittle conditions; (3) The specimen was loaded at a loading rate of 0.5 mm / min using a hydraulic servo testing machine to obtain the initial load F1, and the crack volume C1 at this time was calculated using CT scanning; (4) Place the damaged specimen after splicing in a microwave oven with its semicircular surface free, and heat it at a microwave power of 700 W for 60 s to provide healing conditions. Then, place the specimen at room temperature to cool. (5) According to steps (2) and (3), the healed specimen is fractured again at -10°C to obtain the fracture force F2 and the crack volume C1. The healing rate is calculated using the healing indices HL and CL: HL = F2 / F1, CL = C2 / C1.
[0029] Example 1: A self-healing asphalt mixture is prepared from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 4 parts of road petroleum asphalt, 0.24 parts of double-layer self-healing microcapsules, 0.07 parts of shape memory polymer fibers, and 0.024 parts of carbonyl iron powder.
[0030] Example 2: A self-healing asphalt mixture is prepared from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 4.5 parts of coal tar, 0.28 parts of double-layer self-healing microcapsules, 0.09 parts of shape memory polymer fibers, and 0.028 parts of carbonyl iron powder.
[0031] Example 3: A self-healing asphalt mixture is prepared from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 5 parts of SBS asphalt, 0.32 parts of double-layer self-healing microcapsules, 0.11 parts of shape memory polymer fibers, and 0.032 parts of carbonyl iron powder.
[0032] Example 4: A self-healing asphalt mixture is prepared from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 5.5 parts of PE modified asphalt, 0.36 parts of double-layer self-healing microcapsules, 0.13 parts of shape memory polymer fibers, and 0.036 parts of carbonyl iron powder.
[0033] Example 5: A self-healing asphalt mixture is prepared from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 6 parts of SBR modified asphalt, 0.4 parts of double-layer self-healing microcapsules, 0.15 parts of shape memory polymer fibers, and 0.004 parts of carbonyl iron powder.
[0034] Comparative Example 1: A common asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 4 parts of road petroleum asphalt; The asphalt is heated to 170°C to reduce its viscosity, and then the aggregate heated to 150°C is mixed with the asphalt and stirred for three minutes before forming.
[0035] Comparative Example 2: An asphalt mixture containing self-healing microcapsules: First, the base asphalt was heated to a molten state at 170°C to ensure its fluidity and uniformity. Then, the self-healing microcapsules were added to the molten asphalt, and then stirred for 50 minutes to promote the uniform dispersion of the healing agent microcapsules in the asphalt matrix. Finally, the mixed modified asphalt was cooled to 140°C and allowed to swell for 20 minutes.
[0036] Comparative Example 3: An asphalt mixture containing shape memory polymer fibers: First, the base asphalt was heated to 170°C until it was completely melted to ensure its good fluidity and miscibility. Subsequently, the shape memory polymer fibers were added to the molten asphalt and stirred vigorously for 50 minutes to ensure that the fibers were evenly dispersed throughout the asphalt matrix to form a stable composite system. Finally, the mixed modified asphalt was placed at 140°C for 20 minutes for swelling development.
[0037] Comparative Example 4: A modified asphalt mixture containing carbonyl iron powder: First, the base asphalt needs to be heated to about 170°C to make it completely molten to ensure the fluidity and mixability of the asphalt. Then, the carbonyl iron powder is evenly sprinkled into the molten asphalt and stirred for 50 minutes to ensure that the carbonyl iron powder can be evenly dispersed in the asphalt matrix to form a stable and uniform composite material. Finally, the asphalt mixture with carbonyl iron powder added is cooled to 140°C and allowed to swell for a certain period of time.
[0038] The asphalt mixtures in Examples 1-5 and Comparative Examples 1-4 were subjected to road performance tests and self-healing tests. The road performance test items included a high temperature rutting test, a low temperature beam bending test (-10°C), a freeze-thaw splitting test, and an immersion Marshall test to test the road performance of the self-healing asphalt mixture of the present invention. The self-healing test included a three-point bending test and a crack healing test, and a comparative analysis was performed with a conventional asphalt mixture. The test results are shown in Table 1.
[0039] Table 1 Asphalt mixture road performance test and self-healing test .
[0040] As can be seen from Table 1, the dynamic stability of the self-healing asphalt mixture is much greater than that of ordinary asphalt (Comparative Example 1), indicating that the high-temperature stability of the self-healing asphalt mixture is stronger than that of ordinary asphalt; the maximum flexural strain of the self-healing asphalt mixture is much greater than that of ordinary asphalt, indicating that the strain capacity of the self-healing asphalt mixture when subjected to tension is stronger; the residual stability of the self-healing asphalt mixture is greater than that of ordinary asphalt, indicating that the durability of the self-healing asphalt mixture is stronger than that of ordinary asphalt; the freeze-thaw splitting strength ratio of the self-healing asphalt mixture is greater than that of ordinary asphalt, indicating that the self-healing asphalt mixture has higher water stability and low-temperature crack resistance; the maximum load ratio of the self-healing asphalt mixture is much greater than that of ordinary asphalt, indicating that the self-healing asphalt mixture can withstand higher loads without damage; the crack healing rate of the self-healing asphalt mixture is much greater than that of ordinary asphalt, indicating that the self-healing asphalt mixture has higher self-healing performance.
[0041] The self-healing asphalt mixture in the technical solution of the present application has excellent performance in various key performance indicators, which profoundly demonstrates the interaction between the double-layer self-healing microcapsules, shape memory fibers and carbonyl iron powder. Compared with the asphalt mixture in comparative examples 2-4, the self-healing asphalt mixture (especially Examples 3-5) has not only been greatly improved in dynamic stability, maximum flexural strain, residual stability, freeze-thaw splitting strength ratio and maximum load ratio, but also the crack healing rate has been significantly improved, which has significantly enhanced the comprehensive performance of the asphalt mixture, which is specifically manifested in the following aspects: The significant improvement in dynamic stability shows that the self-healing asphalt mixture can more effectively resist rutting and deformation when facing continuous traffic loads, maintain the flatness and structural stability of the road surface, and extend the service life of the road; the enhancement of the maximum flexural strain enables the mixture to maintain good flexibility and crack resistance when dealing with extreme temperature changes and complex stress conditions, thereby ensuring driving safety. The optimization of residual stability and freeze-thaw splitting strength ratio further demonstrates the outstanding performance of self-healing asphalt mixture under adverse climatic conditions. After multiple freeze-thaw cycles, the mixture can still maintain high strength stability and water damage resistance, effectively resist the occurrence of frost heave cracking and other problems, and improve the overall durability and use quality of the road. The increase in the maximum load ratio is a direct affirmation of the bearing capacity of the mixture, indicating that the self-healing asphalt mixture can still maintain structural integrity and stability when subjected to greater external loads, providing reliable protection for heavy-load traffic and high-intensity use scenarios. The significant improvement in the crack healing rate indicates that through the intelligent repair mechanism of the double-layer self-healing microcapsules, the stress dispersion effect of the shape memory fiber and the auxiliary acceleration effect of the carbonyl iron powder, the self-healing asphalt mixture can respond quickly after the cracks occur and achieve self-repair, which greatly reduces the cost and difficulty of road maintenance and extends the maintenance cycle of the road surface.
[0042] The self-healing asphalt mixture of this application meets the relevant requirements of the Ministry of Transport's standard JTG F40-2004 "Technical Specifications for Highway Asphalt Pavement Construction". Its high temperature stability, low temperature crack resistance, water stability, maximum load ratio and crack healing rate are significantly higher than those of ordinary asphalt, indicating that the asphalt mixture provided in this application has superior road performance.
[0043] The present application has been described in detail above in conjunction with the embodiments; however, those skilled in the art will appreciate that, without departing from the spirit and scope of the present invention, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.
Claims
1. A double-layer self-healing microcapsule, characterized in that: From the outside to the inside, it includes a heat-sensitive shell, a capsule shell and a healing agent filled in the capsule shell; the capsule shell is formed by curing a polycarbonate organic solution, and the heat-sensitive shell is formed by curing a polyvinyl alcohol solution; in terms of mass percentage, the healing agent is formed by mixing and emulsifying 45-55% of hydrogenated bisphenol A epoxy resin and 45-55% of pentaerythritol tetrakis-3-mercaptopropionate.
2. The double-layer self-healing microcapsule according to claim 1, characterized in that: The mass fraction of the polycarbonate organic solution is 70-80%; the mass fraction of the polyvinyl alcohol solution is 20-30%.
3. The method for preparing the double-layer self-healing microcapsule according to claim 1, characterized in that: The steps include: (1) mixing hydrogenated bisphenol A epoxy resin and pentaerythritol tetrakis-3-mercaptopropionate to form an emulsion; (2) adding the emulsion dropwise to a rotating polycarbonate organic solution so that the polycarbonate organic solution wraps the emulsion droplets, and then volatilizing and removing the organic solvent to solidify and form a capsule shell to obtain a microcapsule suspension; (3) After emulsifying the obtained microcapsule suspension to form a stable emulsion, the emulsion is added into a polyvinyl alcohol aqueous solution and the temperature is adjusted to 20-25° C. so that the polyvinyl alcohol solidifies outside the capsule shell to form a heat-sensitive shell, thereby obtaining a microcapsule suspension; (4) The microcapsule suspension obtained in step (3) is washed, centrifuged at 4500-5500 rpm for 12-18 min, and then filtered and dried to obtain double-layer self-healing microcapsules.
4. A self-healing asphalt mixture, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 4-6 parts of asphalt, 0.2-0.4 parts of the double-layer self-healing microcapsule according to claim 1, 0.05-0.15 parts of shape memory polymer fiber, and 0.02-0.04 parts of carbonyl iron powder.
5. The self-healing asphalt mixture according to claim 4, characterized in that: The invention is made of the following raw materials in parts by weight: 100 parts of mineral material, 5.0 parts of asphalt, 0.3 parts of the double-layer self-healing microcapsule according to claim 1, 0.1 parts of shape memory polymer fiber and 0.03 parts of carbonyl iron powder.
6. The self-healing asphalt mixture according to claim 4, characterized in that: The asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt or SBR modified asphalt.
7. The self-healing asphalt mixture according to claim 4, characterized in that: The mineral material consists of coarse aggregate, fine aggregate and mineral powder.
8. The self-healing asphalt mixture according to claim 4, characterized in that: The shape memory polymer fiber is a polyurethane shape memory fiber.
9. The method for preparing the self-healing asphalt mixture according to claim 4, characterized in that: The steps include: (1) A double-layer self-healing microcapsule is prepared according to claim 1; (2) Preparation of carbonyl iron powder modifier: Dry the carbonyl iron powder at 140-160°C for 35-45 minutes for dehydration; (3) Preparation of composite modified asphalt: heat the asphalt to melt at 170-190°C, then add double-layer self-healing microcapsules, shape memory polymer fibers and carbonyl iron powder at 35-45°C, then stir at 170-190°C for 55-65 min, and finally place it at 145-165°C for swelling and development for 25-35 min. (4) Preparation of self-healing asphalt mixture: Mix the mineral material heated to 175°C to 180°C and the composite modified asphalt and stir them evenly to obtain the self-healing asphalt mixture.
10. The preparation method according to claim 9, characterized in that: In the step (3), after the composite modified asphalt is prepared, it is cooled by gradual cooling; the stirring method is magnetic stirring, first stirring at a stirring rate of 4000 to 5000 r / min for 15 to 25 minutes, and then stirring at a stirring rate of 5000 to 6000 r / min for 35 to 45 minutes.
Citation Information
Cited By
Selective multi-stimulus-response self-healing SMP fiber micro-expansion grouting material as well as preparation method and application thereof
CN121342439A
Selective multi-stimulus responsive self-healing SMP fiber micro-expansion grouting material, its preparation method, and applications
CN121342439B
